Evaluasi Implementasi Pelatihan Kerja di Unit Pelaksana Teknis Balai Latihan Kerja Kabupaten Kapuas - Haris Saputa Noordi; H. Suyanto; Ade Hermawan (Administraus, 2018)
The purpose of this study is to evaluate how the implementation of job training in the Technical Implementation Unit of the Kapuas Training Center in Kapuas Regency analyzes what constraints are encountered in the implementation of job training and makes solutions / problems solving constraints inimplementation. This research uses Qualitative Descriptive method. The population in this research as a whole consists of 40 (forty) people involved in the implementation of training year 2016 at UPT Training Center Kapuas Regency, Samples selected by purposive, research data collected by using interview technique to Key Informants, questionnaires to informants and document analysis, data analysis using interactive analysis model. The results of this study indicate that Implementation of the evaluation of the implementation of job training in the Technical Implementation Unit (UPT) Kapuas Training Center has been running well enough, this is evidenced by the enthusiasm of former participants Vocational Computer Training and Sewing Classes Year 2016 to provide opinions on the implementation of job training as well The results of the questions that have been collected showed very positive training activities implemented, which means the implementation of training is good enough, The obstacles encountered in the implementation of job training include: 1). Duration of training that impacts on the effectiveness of the implementation of job training; 2). Workers Instructor training; and 3). Lack of facilities or infrastructure of training facilities, The solution to these obstacles are: a). The existence of policies and additional local and central government budgets to prioritize improving the quality of local human resources in Kapuas district in particular in order to compete with workers from outside the region through a competency-based training program implemented through the Technical Implementation Unit of Kapuas Training Center Kapuas; B). The need for a revision of the standard time of implementation of competency-based training to comply with the rules set by the central government; C). The need for the addition of trainer candidates through the transfer of functions according to the required vocational training; D). The need for local governments and centers for the addition of facilities or infrastructure of training facilities; E). The need for local and central government in the addition of work equipment in accordance with the standards of the establishment of BLK compiled by the Ministry of Labor of the Republic of Indonesia. Tujuan Penelitian ini adalah untuk mengevaluasi bagaimana implementasi pelatihan kerja di Unit Pelaksana Teknis Balai Latihan Kerja Kabupaten Kapuas, menganalisis tentang kendala-kendala apa saja yang ditemui dalam implementasi pelatihan kerja dan membuat solusi/pemecahan masalah terhadap kendala-kendala dalam implementasi.Metode Penelitian ini menggunakan metode Deskriptif Kualitatif, Populasi dalam penelitian ini secara keseluruhan berjumlah 40 (empat puluh) orang yang terlibat dalam pelaksanaan pelatihan tahun anggaran 2016 di UPT Balai Latihan Kerja Kabupaten Kapuas, Sampel dipilih secara purposive, data penelitian dikumpulkan dengan menggunakan teknik wawancara terhadap Key Informan, angket terhadap informan dan analisis dokumen, analisis data menggunakan model analisis interaktif.Hasil penelitian ini menunjukkan bahwa Pelaksanaan evaluasi implementasi pelatihan kerja di Unit Pelaksana Teknis (UPT) Balai Latihan Kerja Kapuas sudah berjalan dengan cukup baik, ini dibuktikan dengan antusiasnya eks peserta pelatihan kejuruan Operator Komputer dan Menjahit angkatan Tahun 2016 untuk memberikan pendapatnya mengenai implementasi pelatihan kerja serta hasil dari pertanyaan yang telah dihimpun menunjukan sangat positifnya kegiatan pelatihan yang dilaksanakan, yang berarti implementasi pelatihan kerja sudah cukup baik, Kendala-kendala yang ditemui dalam implementasi pelatihan kerja antara lain: 1). Lama waktu pelatihan yang berimbas kepada efektivitas implementasi pelatihan kerja; 2). Tenaga Instruktur pelatihan kerja; dan 3). Kurangnya fasilitas atau prasarana sarana pelatihan kerja, Adapun solusi terhadap kendala-kendala tersebut adalah: a). Adanya kebijakan dan penambahan anggaran pemerintah daerah dan pusat untuk lebih mengedepankan peningkatan kualitas SDM lokal yang ada di Kabupaten Kapuas pada khususnya agar dapat bersaing dengan tenaga kerja dari luar daerah melalui program pelatihan berbasis kompetensi yang dilaksanakan melalu Unit Pelaksana Teknis Balai Latihan Kerja Kapuas; b). Perlunya revisi mengenai standar waktu pelaksanaan pelatihan berbasis kompetensi agar sesuai peraturan yang telah ditetapkan oleh pemerintah pusat; c). Perlunya penambahan calon tenaga instruktur melalu alih fungsi sesuai kejuruan pelatihan kerja yang dibutuhkan; d). Perlunya pemerintah daerah dan pusat penambahan fasilitas atau prasarana sarana pelatihan kerja; e). Perlunya pemerintah daerah dan pusat dalam penambahan peralatan kerja yang sesuai dengan standar pendirian BLK yang disusun oleh Kementerian Ketenagakerjaan RI.